Diagnóstico da unidade de Auditoria Interna da Universidade Federal da Paraíba a partir da análise das forças, fraquezas, ameaças e oportunidades (Análise SWOT) - Gomes, Cláudia Suely Ferreira (2019)
Strategic planning is an essential management tool for the development of organizations, whether public or private, and its use in government internal audit can contribute to maximizing their operational results. From this perspective, this research aimed to carry out an environmental diagnosis in the Internal Audit Unit of UFPB, using the SWOT analysis (diagnosis of strengths, weaknesses, threats, and opportunities), to support the implementation of the strategic planning of the Unit from 2020. The proposed strategic planning model, the final product of this dissertation, presented an environmental diagnosis, which pointed out the internal and external aspects that may influence the performance of the activities performed in the referred Unit. To achieve the goals set, qualitative approach research was applied, using direct observation and documentary research as data collection techniques. The instruments used in the planning of internal audit activities, issued between 2016 and 2018, characterizing the research universe were analyzed. The theoretical framework is based on the main concepts related to the Brazilian public administration and internal government audit, in addition to the normative basis that underlies the internal government audit, such as laws, decrees, normative instructions, technical manuals and other legal instruments relevant to the subject matter study. The results of the research revealed that SWOT analysis is an important strategic tool for a governmental internal audit because, from an approach based on the identification of the main factors that may interfere with the quality of the work performed, it provides essential elements for the preparation of its planning as well as decision-making to optimize their performance.